If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+7x+2x=23
We move all terms to the left:
1+7x+2x-(23)=0
We add all the numbers together, and all the variables
9x-22=0
We move all terms containing x to the left, all other terms to the right
9x=22
x=22/9
x=2+4/9
| k^2/3=4 | | |4x+7|=2x-6 | | 286-y=87 | | 205=154-w | | 295=-x+91 | | 80(0.75x)=10 | | 3/4n+3)=9 | | 3/x=6/(x+8) | | 10x=49+3x | | 6=-5/9+u | | 0.5w=25 | | 4^5x=410 | | z=-1(3)-5 | | 2b+3b=15 | | 8a+11=64 | | -4.5z-7.2=-3.3z | | 4+5(p-1)=36 | | 4+5(p+1)=36 | | 3(x-3)+14=2x+8 | | 4(5x+2)+2(2×+2)=180 | | (5x+10)=-7 | | 6(5x+2)+9(2x+8)=204 | | 3(7x+5)+8(4x+2)=296 | | 4(5x+2)+2(2x+2)=180 | | 2x•13/12=x | | 2y-(-10)=-16 | | 7y^2-6=94 | | 4/5x-4=16 | | 5x=5=25 | | 9x=7(x+2 | | -23z-0.3=33z+2.6 | | 20=5/3y |